Size multipartite Ramsey numbers for stripes versus small cycles - Chula Janak Jayawardene; Edy Tri Baskoro; Lilanthi Samarasekara; Syafrizal Sy (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2016)
For simple graphs G_1 and G_2, the size Ramsey multipartite number m_j(G_1, G_2) is defined as the smallest natural number s such that any arbitrary two coloring of the graph K_j × s using the colors red and blue, contains a red G_1 or a blue G_2 as subgraphs. In this paper, we obtain the exact values of the size Ramsey numbers m_j(nK_2, C_m) for j 2 and m {3,4,5,6}.